Pengaruh Pendekatan Kontekstual terhadap Peningkatan Minat Belajar Kimia Peserta Didik - Dwiani Ratna Sari; Syaza Syahana; Lisya Asmiati; Elma Pujiana; Suyanta Suyanta (Postgraduate, University of Mataram, 2023)
Chemistry is considered an abstract discipline, characterized by many concepts that make students uninterested in engaging in its learning. One approach to stimulate interest is through the application of contextual learning, where acquired knowledge is applied in a practical context. The purpose of this journal review is to provide insight into the implications of using contextual approaches in chemistry education, particularly about fostering student interest and engagement in the subject matter. The research design used in this study was a systematic literature review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) as a tool and guide for evaluating articles. The search for articles published in Scopus and Web of Science using the selected keywords: contextual approach, learning interest, and its extension based on the selected PICO framework. Based on the search results, 50 articles were obtained to be analyzed. Findings from diverse data consistently show that the application of contextual or everyday learning approaches contributes to increasing students' interest in learning, especially in the chemistry domain. Students' interest in learning chemistry has a significant influence on their learning outcomes, motivation, and critical thinking levels. This is because the greater the student's interest in learning chemistry, the stronger the curiosity and understanding of the subject matter. When students have a strong understanding of the subject matter, their critical thinking skills and chemical learning outcomes improve.